Forecasting renewable hydrogen production technology shares under cost uncertainty. (5th August 2021) - Lane, Blake; Reed, Jeffrey; Shaffer, Brendan; Samuelsen, Scott
Abstract: This analysis applies a novel learning-curve methodology with uncertainty through Monte Carlo simulation to forecast market share of competing renewable fuel production technologies from 2025 through 2050. The analysis incorporates uncertainty in technology learning rate within Wright's Law, market rate of growth, and project-specific bidding to develop build-out scenarios for renewable hydrogen production capacity to serve the global market through 2050 with California as a proxy. Two major hydrogen production technologies are included: electrolyzers (with proton exchange membrane electrolytic cells as proxies) and thermochemical devices (with gasifiers as proxies). The method provides a quantitative foundation to forecasting technology shares in emerging sectors, overcomes the weakness of point estimates of relative cost that generally lead to binary behavior, and can support policy development and assessment of community impacts associated with the large-scale facility build-out needed to serve the growing demand for renewable hydrogen in transportation and other applications. Results show that biomass gasifiers are the dominant technology in the early market but the higher learning rate of electrolyzers and long-term trend of price decline for renewable electricity leads to equal shares for new installations by the mid-term and eventually to electrolyzers having the dominant share of new facilities. Electricity, biomass, and initial gasifier technology costs are the three primary factors impacting 2050 renewable hydrogen market composition. Highlights: Novel method to project fuel production technology shares with uncertainty proposed. Methodology recognizes variability in technology cost at a point in time. Methodology overcomes single winner outcome of point estimates of future cost. Electrolyzers are projected to increase in market share continually from 2025. Feedstock and initial gasifier costs impact 2050 market composition the most.